2022
DOI: 10.1101/2022.10.09.511500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stripes and loss of color in ball pythons (Python regius) are associated with variants affecting endothelin signaling

Abstract: Color patterns in non-avian reptiles are beautifully diverse, but little is known about the genetics and development of these patterns. Here we investigated color patterning in pet ball pythons (Python regius), which have been bred to show color phenotypes that differ dramatically from the wildtype form. We report that several color phenotypes in pet animals are associated with putative loss-of-function variants in the gene encoding endothelin receptor EDNRB1: (i) frameshift variants in EDNRB1 are associated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(323 reference statements)
0
1
0
Order By: Relevance
“…This observation is interesting, as a black-striped pattern is visible in adult C. marthae, the only species of iguana in the Galápagos whose hatchlings present green areas in their skin. Recently, Dao and collaborators (40) showed that several color phenotypes in the snake Python regius, including dorsal striping, are associated with putative loss-of-function variants in the gene encoding endothelin receptor EDNRB2. Overall, these studies provide an important conceptual background for future investigation of the peculiar phenotypic color traits in the pink iguana.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is interesting, as a black-striped pattern is visible in adult C. marthae, the only species of iguana in the Galápagos whose hatchlings present green areas in their skin. Recently, Dao and collaborators (40) showed that several color phenotypes in the snake Python regius, including dorsal striping, are associated with putative loss-of-function variants in the gene encoding endothelin receptor EDNRB2. Overall, these studies provide an important conceptual background for future investigation of the peculiar phenotypic color traits in the pink iguana.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging model for genetic studies in reptiles is the ball python (P. regius) (Brown et al 2022;Garcia-Elfring et al 2023;Dao et al 2023). Ball pythons are native to west Africa, but have become common as pets.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach was to collect samples of pet ball pythons (shed skins) from across the United States and search for putative loss-of-function variants in the melanophilin gene. A similar approach has been used previously by our group to identify variants controlling melanin production (Brown et al 2022) and patterning (Dao et al 2023).…”
Section: Introductionmentioning
confidence: 99%